Noise Characteristics of a Superlattice Avalanche Region IMPATT Diode - Prasad Rao K.S.V.S.N.; Pal B.B.; Khan R.U. (My University, 2025)
The intrinsic noise characteristics of a recently proposed AlGaAs/GaAs superlattice avalanche region IMPATT diode has been presented. The open circuit noise voltage, excess noise factor, signal to noise ratio and the ratio of multiplication noise to shot noise have been calculated and discussed. The noise is found to be reduced significantly due to the superlattice structure of the device. © 1996 Taylor & Francis Group, LLC.